Autonomous Information Behaviour: Towards a Conceptual Model - Ridley, Michael (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2019)
Autonomous information behaviour (AIB) proposes that autonomous intelligent agents exhibit information behaviour characteristics (i.e. “need, seek, manage, give, and use information in different contexts” Fisher, Erdelez, & McKechnie, 2005, p. xix) similar to that in humans. A preliminary conceptual model of AIB, derived from Wilson (2016) and Domingos (2015), is presented. Understanding autonomous information behaviour is important given the increasing prevalence of algorithmic decision-making in everyday life.